2023
DOI: 10.3390/vetsci10050366
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Use in Canadian Cow–Calf Herds

Jayce D. Fossen,
John R. Campbell,
Sheryl P. Gow
et al.

Abstract: Despite growing concern surrounding antimicrobial use (AMU) and the importance of cow–calf herds to the Canadian livestock industry, surveillance of AMU in cow–calf herds to inform antimicrobial stewardship programs has been sporadic. Producers from the Canadian Cow–Calf Surveillance Network (87%, 146/168) provided data and almost all reported AMU in at least one animal (99%, 145/146 herds) in 2019–2020. The most common reasons for AMU were treatment of respiratory disease in nursing calves in 78% of herds and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…The C3SN is also the first pan-Canadian study to collect longitudinal data on treatment for the most commonly reported calfhood diseases and reasons for AMU, in addition to death loss in cow-calf herds for both the first month of life and for the period from birth to weaning ( 26 ). Differences in treatments between cows and heifers were not requested due to concerns about whether producers would be able to easily provide those data.…”
Section: Discussionmentioning
confidence: 99%
“…The C3SN is also the first pan-Canadian study to collect longitudinal data on treatment for the most commonly reported calfhood diseases and reasons for AMU, in addition to death loss in cow-calf herds for both the first month of life and for the period from birth to weaning ( 26 ). Differences in treatments between cows and heifers were not requested due to concerns about whether producers would be able to easily provide those data.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, the use of virginiamycin is approved for use in cattle being fed for slaughter to help reduce liver abscesses [ 39 ]. However, virginiamycin use has not been reported in cow-calf herds [ 17 ]. A single sampled herd had an associated feedlot allowing for potential limited exposure [ 17 ]; however, no virginiamycin use was reported in any of the sampled herds in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…However, virginiamycin use has not been reported in cow-calf herds [ 17 ]. A single sampled herd had an associated feedlot allowing for potential limited exposure [ 17 ]; however, no virginiamycin use was reported in any of the sampled herds in 2020. Resistance to quinupristin/dalfopristin varied between herds with herd of origin having a slight impact on resistance for E. casseliflavus .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations